The intervention on aging system: A classification model, the requirement for five novel categories - Palmer, Raymond D. (Aging medicine, 2022)
Aging is widely considered an immovable fact of life. Cultural conditioning has ensured that therapeutics for extreme human lifespans are considered out of reach technologies. However, longevity therapies such as stem cell replacement, fasting, gene therapies, fasting mimetics such as metformin and rapamycin, regulation and tissue reprogramming with OSK transcription factors, blood dilution, metabolic pathway engineering, reversal of epigenetic drift, heterochronic parabiosis, coenzyme replacement technologies (nicotinamide adenine dinucleotide) and a plethora of other established sciences are showing great potential at slowing down the rate at which tissues enter dysfunction. Recent discoveries have shed light on major mysteries of the aging process. Longevity‐based discoveries are not only landing quickly, but therapies to prevent or reverse those drivers of aging are also being devised regularly and this is opening up an entirely new industry, the longevity industry. This presents the requirement for a new classification system where subjects can be divided into specific groups based on their potential for mortality. This system also enables the public to target which class of this classification system they wish to be on. Moving the population on the classification system to become more disease resistant holds great benefit for society and governments as a whole. The upward curve reflects the vision for humanity to pursue healthier living.